Gender association of restorative techniques performed for class II cavities in university hospital. - R, BHARATHI; S, DEEPAK; MURUGAN P, SENTHIL (The journal of contemporary issues in business and government, 2021)
Class II dental caries involve decay of the proximal surfaces of premolars and molars. The most commonly used direct restoration techniques are amalgam and composite restoration which is directly performed onto the tooth to be restored. Teeth also can be restored using indirect techniques in which restorations are fabricated outside of the mouth.The most common indirect restoration techniques are cast metal and cast ceramic restorations. The aim of this study was to evaluate the gender association of restorative techniques performed for class II cavities in university hospital. Data of the patients were retrieved from the dental records. Patients with class II caries were shortlisted, gender and restoration techniques were studied. Total study sample was 1182 cases. Data was tabulated in excel and statistically analysed using the Chi Square test. In class II caries, amalgam restoration technique (79.7%) was the most commonly performed restoration technique followed by composite restoration technique (17.6%) and cast restoration technique (2.6%). This indicated that the most commonly performed technique was the direct restoration technique (97.4%) followed by indirect restoration technique (2.6%) and there was no significant gender association among the various types of fillings (P.0.05- chi square- statistically not significant). Within the limitation of this study, in patients with class II caries, the most commonly performed technique was the amalgam restoration technique followed by composite and cast restoration technique and there was no significant gender association among the restorations performed in this institutional study.